Evapotranspiration covers at uranium mill tailings sites. Issue 5 (15th July 2022) - Caldwell, Todd G.; Tabatabai, Sarah; Huntington, Jena M.; Davies, Gwendolyn E.; Fuhrmann, Mark
Abstract: Waste isolation is a key strategy for mitigating risk from municipal solid waste (MSW) and hazardous waste streams. Conventional covers at MSW facilities are designed for a 30‐yr post‐closure period where compacted soils and geosynthetics are used to minimize percolation into buried waste. Recently, evapotranspiration (ET) covers have shown beneficial use for MSW management. Evapotranspiration covers encourage infiltration, storage, and transpiration of precipitation to minimize percolation. Such covers may also have beneficial use for long‐term waste issues, such as at Uranium Mill Tailings Radiation Control Act (UMTRCA) sites. These sites were covered by a clay radon barrier to create tortuous flow paths that allow radioactive decay and attenuation of short‐lived, radon‐222 gas. For long‐term waste isolation, an ET‐radon cover may provide greater resilience by exploiting natural processes instead of resisting them. This update presents a review of the current state‐of‐the‐science regarding ET covers and considerations for long‐term applications. Core Ideas: Conventional cover designs assume that engineering properties are static in time. Evapotranspiration (ET) covers integrate natural hydrologic and ecologic processes into the design. ET covers may provide improved resilience at long‐term disposal sites with radon barriers. Scientific basis and regulatory implications of using ET covers at long‐term disposal sites.